A comparative study of destructive effects resulting from road profile acting on off-road towed vehicles. (February 2019) - Gurmai, László; Kiss, Péter
Highlights: On various obstacles, the vibrational excitation effect was measured on a trailer. Based on a trailer mechanical model the transmission characteristics was determined. A method was elaborated of the forces acting on vehicles under different terrain conditions. A method was developed of comparing various stochastic road profiles. Abstract: The more extreme conditions the vehicle is exposed to, the sooner it wears out and deteriorates. In order to determine the forces affecting the lifespan of vehicles we need to know the environmental conditions eliciting these forces. This research aims at elaborating and testing a method which can help to conduct a comparative analysis of forces acting on towed vehicles used in different terrain conditions. Excitation forces acting on a vehicle being towed across terrain cause vibrations which lead to wear and structural deterioration. The rate of deterioration depends on the activating forces resulting from the road profile geometry and the dynamic properties of the vehicle. A knowledge of the relationship between the towed vehicle and the terrain profile will enable the design of an artificial road profile for fatigue testing with which similar stresses arise as during normal use. With the developed comparative method, a connection can be established between stochastic road profiles and road profiles containing artificially built obstacles.